Late Quaternary right-lateral slip rate along the Tangyuan segment of the Yilan–Yitong Fault Zone on the NE China Plain - Yu, Zhongyuan; Yin, Na; Yang, Yanlin; Li, Luwei; Ma, Yanli (Frontiers in Earth Science, 2024)
The slip rate of strike-slip active faults is crucial for fault rupture behavior analysis and seismic hazard assessment. Although many segments of the Yilan–Yitong Fault Zone (YYFZ) in NE China have been strongly deformed since the late Quaternary, little progress has been made on its slip rate. With the help of high-resolution satellite images, detailed field investigations, seismic reflections, and Quaternary chronological dating, we mainly studied the late Quaternary right-slip rate of the YYFZ. Field investigations revealed an ∼15 km long by ∼1–2 m high-surface scarp belt extending along the Tangyuan graben interior, with a series of sag ponds and small parallel bulges. Research has revealed that the most recent paleoearthquake (∼M 7.0) occurred between 2,800± 600 a BP and 1,700 ± 200 a BP, with evidence of coseismic surface rupture. The T2 terrace abandonment age of the Heijin River is approximately 55.13 ± 1.78 ka (OSL), and the maximum cumulative right-lateral offset may reach 110 ± 5 m. Thus, the maximum right-slip rate of the Tangyuan segment of the YYFZ since the late Quaternary is constrained to 1–2 mm/a according to the upper terrace model. This study suggests that the presence of a new fault in the basin interior merits more attention when assessing the influential surface range and earthquake potential along the YYFZ, and the features of “low tectonic loading rate, activity migration in space, and clustering in time separated by ten thousand years of seismic quiescence” observed along the YYFZ are highly important for earthquake model construction and tectonic deformation studies in stable continental regions (SCRs).